Freshwater Red Algae: Phylogeny, taxonomy and biogeography - Vis, Morgan L; Necchi, Orlando [UNESP] (My University, 2022)
This book presents the phylogeny, taxonomy and biogeography of freshwater red algae. Its content is divided into five chapters. The first chapter provides a brief history of freshwater red algal research, habits and collecting methods, general biogeographic trends and an overview of the taxonomic/phylogenetic placement of freshwater taxa. The other four chapters are taxonomic treatments of non-marine red algae based on taxonomic levels, i.e. classes within the phylum Rhodophyta, orders within each class, families within each order, and genera within each family. Descriptions, phylogenetic data (including numerous trees), geographic range (maps for most species) and dichotomous keys for identification are presented. Comprehensive data are provided for more than 220 species.
Keywords: Batrachospermales; Freshwater ecology; Limnology; Phycology; Rhodophyta; Thoreales